A systematic study of molecular diagnosis, treatment, and prognosis in infant-type hemispheric glioma: an individual patient data meta-analysis of 164 patients - Chavaz, Lara; Bagchi, Aditi; Dhanda, Sandeep K; Toutain, Fabienne; Pfister, Stefan M; Sturm, Dominik; Pietsch, Torsten; Gielen, Gerrit H; Waha, Andreas; Clarke, Matthew; Lu, Congyu; Karremann, Michael; et al. (Neuro-Oncology, 2026)
Due to the novelty and rarity of infant-type hemispheric glioma (IHG), optimal treatment and factors determining clinical outcomes are yet to be established.We curated a series of 164 patients with IHG; 155 identified by methodical literature search and nine additional patients contributed by collaborators.All tumors were hemispheric, diagnosed at a median age of 3.4 (0-52) months, and frequently (95%) non-metastatic. One hundred forty-two (86.5%) tumors harbored fusions involving receptor tyrosine kinase (RTK) genes (ALK [67/142, 47%], NTRK1/2/3 [32/142, 22.5%], ROS1 [29/142, 20.4%], MET [13/142, 9.2%], and ABL2 [1/142, 0.7%]). Sixty-four percentage, 20%, and 8% of patients were treated with surgery and adjuvant chemotherapy, surgery-only, and surgery plus targeted therapy, respectively. Five patients received radiation. Three-year event-free survival (EFS) and overall survival (OS) was 49.5% [40.7-60.2] and 79.6% [72.1-87.9], respectively. Twenty-two patients succumbed to disease, of which tumor progression (8/22, 36%) and intra-cranial hemorrhage (5/22, 23%) were the most common causes. Multivariate analysis showed that the factors most associated with an increased risk of death were no treatment except for surgery and presence of residual tumor after definitive surgery. These findings present a challenging dichotomy where surgery is both a serious risk factor for early death and, when successful, a benefit.Together, these findings show that IHG is a fusion driven tumor of the very young that is survivable even after progression. While optimal primary therapy for patients with IHG has yet to be established, the findings of this meta-analysis suggest treatment should focus on lowering surgical morbidity and improving its success.
Online veröffentlicht: 8. November 2025
Gesehen am 02.03.2026